Care provided by Family Health Strategy teams in patients at risk of suicide (Research, Society and Development, 2020)
The study aimed to characterize the care provided by two Family Health Strategy (FHS) teams to patients at risk of suicide in a city located in the interior of Rio Grande do Sul (RS). Qualitative and descriptive study, conducted with 15 health professionals from two ESF, through semi-structured interviews with open questions. Data were collected between September and October 2018 and analyzed qualitatively. The results point to the following categories related to care for patients with suicidal behavior: identification of actions taken by the FHS team; difficulties of the FHS team in caring for patients; evaluation by the FHS team regarding the care provided to patients. It is understood that the care for patients with suicidal behavior by FHS teams starts from a good risk assessment in order to, from then on, provide care in a personalized way, also involving practices aimed at families and the community, with preventive measures.